Pengaruh Kompetensi Dan Beban Kerja Terhadap Kinerja Karyawan Di Hotel Neo Dipatiukur Bandung - Hafshah, Syifa Shamaya; Sahlan, Muhammad (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The decline in hotel occupancy in Bandung City during the first quarter of 2025, including at Hotel Neo Dipatiukur, was a consequence of the budget efficiency policy stipulated in the Presidential Instruction of the Republic of Indonesia Number 1 of 2025. This policy resulted in the reduction of daily labor staff, leading to increased workloads for permanent employees, some of whom were assigned tasks beyond their core competencies. Such conditions have the potential to negatively impact employee performance. This study aims to examine the conditions of employee competence, workload, and performance at Hotel Neo Dipatiukur, as well as to analyze the influence of competence and workload on employee performance. The research employed a descriptive-verificative method with a quantitative survey approach. The sample comprised 32 permanent employees selected using a saturated sampling technique. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that employees’ perceptions of competence, workload, and performance at Hotel Neo Dipatiukur are generally very good, although there remains room for improvement to optimize work outcomes and task management. The findings demonstrate that an increase in employee competence is positively correlated with improved performance, while a decrease in competence may reduce performance. Similarly, optimal workload management has a significant positive effect on performance, whereas disproportionate workload can adversely affect it. Partially, competence and workload contribute to performance improvements by 0.454 and 0.958 units, respectively. Simultaneously, these two variables explain 79.2% of the variance in employee performance, with the remaining 20.8% influenced by factors beyond the scope of this study.